Rationale and design of the CRAFT (Continuous ReAssessment with Flexible ExTension in Rare Malignancies) multicenter phase II trial - Heilig, Christoph E.; Horak, Peter; Kreutzfeldt, Simon; Teleanu, Maria-Veronica; Mock, Andreas; Renner, Marcus; Bhatti, Irfan A.; Hutter, Barbara; Hüllein, Jennifer; Fröhlich, Martina; Uhrig, Sebastian; Süße, Heike; et al. (ESMO open, 2021)
Background - Approvals of cancer therapeutics are primarily disease entity specific. Current molecular diagnostic approaches frequently identify actionable alterations in rare cancers or rare subtypes of common cancers for which the corresponding treatments are not approved and unavailable within clinical trials due to entity-related eligibility criteria. Access may be negotiated with health insurances. However, approval rates vary, and critical information required for a scientific evaluation of treatment-associated risks and benefits is not systematically collected. Thus clinical trials with optimized patient selection and comprehensive molecular characterization are essential for translating experimental treatments into standard care. - Patients and methods - Continuous ReAssessment with Flexible ExTension in Rare Malignancies (CRAFT) is an open-label phase II trial for adults with pretreated, locally advanced, or metastatic solid tumors. Based on the evaluation by a molecular tumor board, patients are assigned to combinations of six molecularly targeted agents and a programmed death-ligand 1 (PD-L1) antagonist within seven study arms focusing on (i) BRAF V600 mutations; (ii) ERBB2 amplification and/or overexpression, activating ERBB2 mutations; (iii) ALK rearrangements, activating ALK mutations; (iv and v) activating PIK3CA and AKT mutations, other aberrations predicting increased PI3K-AKT pathway activity; (vi) aberrations predicting increased RAF-MEK-ERK pathway activity; (vii) high tumor mutational burden and other alterations predicting sensitivity to PD-L1 inhibition. The primary endpoint is the disease control rate (DCR) at week 16; secondary and exploratory endpoints include the progression-free survival ratio, overall survival, and patient-reported outcomes. Using Simon’s optimal two-stage design, 14 patients are accrued for each study arm. If three or fewer patients achieve disease control, the study arm is stopped. Otherwise, 11 additional patients are accrued. If the DCR exceeds 7 of 25 patients, the null hypothesis is rejected for the respective study arm. - Conclusions - CRAFT was activated in October 2021 and will recruit at 10 centers in Germany. - Trial registration numbers - EudraCT: 2019-003192-18; ClinicalTrials.gov: NCT04551521.
Gesehen am 24.01.2023